APATITE, MONAZITE, AND XENOTIME IN METAMORPHIC ROCKS - Spear F.S.; Pyle J.M. (My University, 2002)
This chapter focuses on phosphates that are significant in metamorphic rocks. A quick survey of phosphate mineral descriptions at a commercial mineral web-site revealed over 500 phosphate mineral names. Remarkably, only three are common in metamorphic rocks: apatite, monazite, and xenotime, and this chapter is restricted to discussion of these minerals. Apatite, monazite, and, to a lesser extent, xenotime, have enjoyed intensive study during the previous half-century. Following World War II, considerable study was made of minerals that contain fissionable materials, and the sometimes large concentrations of U and Th in monazite culminated in a number of seminal papers on the occurrence of that mineral (e.g., Overstreet 1967). During the 1970s and early 1980s, the study of apatite and monazite turned towards their role as a sink for REEs and other trace elements in rocks (e.g. Watson 1980, Watson and Capobianco 1981). Throughout this period, monazite (and to some extent xenotime) enjoyed attention as a geochronometer (e.g., Parrish 1990), and through today this attention has continued to grow. Accessory minerals such as monazite, xenotime, and apatite have come to the forefront of research in metamorphic petrology in recent years for two reasons. First, it has recently been recognized that trace elements in metamorphic rocks, and especially trace element zoning in garnet and other major phases, contain considerable detailed information about the reaction history a rock has experienced. Coupled with the fact that diffusion of many trace elements in metamorphic minerals is, in general, considerably slower than diffusion of major elements in those same minerals, the possibility has recently emerged of recovering details of metamorphic petrogenesis that were previously unattainable. Inasmuch as accessory minerals play a dominant role in the mass budget of many trace elements, attention has naturally turned to their paragenesis. It has also recently been discovered that …